SIMULACRA AND REALITY IN AI FILMS: BAUDRILLARD’S ANALYSIS OF ‘M HOTEL’ - Pebriyanto; Athila Raditya Rahman; Muhamad Naufal Raditya (Telkom University, 2025)
M Hotel is a short film produced by artificial intelligence (AI) that has won several awards. This raises questions related to the meaning of reality, authenticity, and subjectivity in its production in the current era of digital technology development. This research employed a qualitative-descriptive approach, integrating visual and narrative text analysis methodologies to examine the film. Jean Baudrillard's theoretical framework of simulacra and hyperreality is employed to analyze how M Hotel not only creates a representation of reality, but also forms a simulation that is detached from its original reference. The findings indicate that the M Hotel has entered the fourth stage of simulacra, wherein reality is substituted by an independent image. The film also indicates a shift in human subjectivity towards aesthetics created through an algorithmic command system that blurs the line between reality and illusion.